Development and validation of a chemotherapy tolerance prediction model for Chinese multiple myeloma patients: The TM frailty score - Chen, Yadong; Gu, Jingli; Huang, Beihui; Liu, Junru; Li, Xiaozhe; Li, Juan (Frontiers in Oncology, 2023)
Objective: The physical fitness of older individuals is heterogeneous, making it difficult to know their chemotherapy tolerance. The toxicities may offset the benefits of anti-myeloma therapy in frail patients. The accurate evaluation of frailty status before chemotherapy is essential. We aimed to explore the applicability of the IMWG GA and develop a new frailty screening tool more suitable for Chinese MM patients. Cases and Methods: We performed the IMWG GA and the full CGA in 167 MM patients and validated the applicability of the IMWG GA to chemotherapy and prognosis. The CGA domains were screened for their predictive value to improve IMWG GA and develop new frailty screening tools. Results: The results showed that the IMWG GA had limitations in distinguishing the risk of grade ≥3 adverse events (AEs) between fit and int-fit patients. Of the CGA domains, TUG and MNA-SF were independent prognostic factors for grade ≥3 AEs and OS and further stratified the risk of grade ≥3 AEs in the IMWG GA int-fit subgroup (P< 0.05). We combined TUG and MNA-SF to construct the TM frailty score. The frail subgroup had a higher proportion of adverse outcomes, a higher hazard ratio (HR) in Cox regression and a higher Harrell's C-index for distinguishing the risk of grade ≥3 AEs and OS than the IMWG GA frail subgroup. Conclusion: The TM frailty score is more suitable than the IMWG GA for evaluating chemotherapy tolerance and prognosis in the Chinese population.